Integrating Competence Assessment, Internal Quality Control, and External Quality Assurance in a Large Point-of-Care Testing Network. Issue 1 (March 2020) - Martin, Cameron; StJohn, Andrew; Badrick, Tony
Abstract : Abstract: Point-of-care testing is widespread and requires a different form of quality control and quality assurance model to conventional laboratory testing because the types of error that occur are different. In many situations, the point-of-care instruments and operators are part of a broader organizational network. We have developed a different model for the provision of a quality framework for these situations. The quality of the instrument cartridges is checked centrally, and the quality assurance is wider in concept assessing the operator competence and instrument operation. Centralizing some of the quality control reduces errors and allows for greater confidence in the results.